1991
DOI: 10.1017/s0266462300005109
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of A Support Program for Caregivers of Demented Elderly

Abstract: An economic evaluation was undertaken concurrently with a randomized trial comparing a Caregiver Support Program (CSP) with existing conventional community nursing care for those caring for elderly relatives at home. The differences in resource consumption were compared with changes in caregiver quality of life, as measured by the Caregiver Quality of Life Instrument (CQLI). A 20% difference from baseline in the CQLI favored the experimental (CSP) group, although this did not reach conventional levels of stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 24 publications
1
56
0
1
Order By: Relevance
“…73 Other 'utility' studies have been reported in the literature; [74][75][76][77][78] however none of them addressed specifically wandering symptoms.…”
Section: Results Of the Systematic Review Of Economic Studiesmentioning
confidence: 99%
“…73 Other 'utility' studies have been reported in the literature; [74][75][76][77][78] however none of them addressed specifically wandering symptoms.…”
Section: Results Of the Systematic Review Of Economic Studiesmentioning
confidence: 99%
“…Furthermore, the diagnoses in mental health care are largely chronic and not lethal, so that successful treatment is not likely to produce a gain in life years. Drummond et al 73 used the QALY measure to assess the care-giver's quality of life, as part of an economic evaluation of a support program for care-givers of the demented elderly. In the study of Kamlet et al, 74 a markovian model was constructed to estimate the quality of life impact of maintenance treatment for recurrent depression.…”
Section: Nature Of Economic Appraisalmentioning
confidence: 99%
“…Similarly, the economic evaluation of a training programme for carers of people with dementia 40 reported cost savings of Aus $7967 (US $5975) per patient, with improved patient survival at home and decreased carer morbidity. Drummond and colleagues 41 evaluated a support programme for carers (RCT) which showed improved quality of life with incremental cost per quality-adjusted lifeyear (QALY) gained of Can $20,000. The evaluation of a daily living programme (RCT) by Knapp and colleagues 42 found that it was more cost-effective than hospital-based care.…”
Section: Cost-effectiveness Of Support For Carersmentioning
confidence: 99%